Acousmatic Orphism: Susan Howe. Issue 3 (September 2021) - Donahue, Joseph
Abstract : In this essay Joseph Donahue uncovers the Orphic ambitions of Susan Howe's 2010 volume of poetry, That This, especially as manifested in the poet's collaboration with the composer David Grubbs in the recording of a poem from that volume, 'Frolic Architecture'. To account for the use of free-floating syllabic sound as an intensification of the Orphic concerns of the poem in the recording, the essay turns at first to the origin of acousmatic sound and its proposed relations to ancient mystery cults: composer and sound theorist Pierre Schaeffer claimed that to hear sound without seeing its source placed the listener in a position comparable to that of an initiate in the cult of Pythagoras. Drawing on Brian Kane's 2014 study of the origins of musique concrète (which incorporates recorded sounds) in the postwar period, Sound Unseen, this piece claims the acousmatic not only for Pythagoras but for Orpheus. It is argued that an Orphic poetics rooted in the acousmatic comes to full fruition in late Howe. Howe's own evocations of Pythagoras, and her own mythologising of the acousmatic, are examined, especially in regard to her collage method which so often and so momentously conceals or removes the visual origin of sounded syllables. The collaboration with composer David Grubbs intensifies the acousmatic poetics of Howe's text, and it is suggested, is the poem's ultimate realisation.